Reversal of a Suspected Paradoxical Reaction to Zopiclone with Flumazenil - Zarah Jordahn; Cheme Andersen; Anne Marie Roust Aaberg; Frank Christian Pott (Case Reports in Critical Care)
We describe the care for an elderly woman who was admitted to the intensive care unit (ICU) to receive noninvasive ventilation for acute exacerbation of chronic obstructive pulmonary disease. After administration of the sleeping pill zopiclone, a nonbenzodiazepine receptor agonist (NBRA), the patient became agitated and was confused, a possible paradoxical reaction to benzodiazepines. These symptoms were immediately resolved after treatment with flumazenil, usually used to reverse the adverse effects of benzodiazepines or NBRAs and to reverse paradoxical reactions to benzodiazepines. This case indicates that zopiclone induced behavioral changes resembling a paradoxical reaction to benzodiazepines and these symptoms may be treated with flumazenil.